Degradação da glicose pelo bacterioplâncton: mineralização e formação de produtos intermediários - Panhota, Rafael Spadaccia (2002)
This study aimed compare the bacterioplankton heterotrofic potential and the routes of glucose mineralization, and also determined some polymeric monossacharides produced by bacterioplankton. Water samples were collected in the Barra Bonita reservoir SP (22º32 34.5 S and 48º29 26.4 W) in two periods (February/01 e July/01), filtered and enriched with glucose. The samples were incubated at 20ºC during 60 days, under aerobic and anaerobic conditions. During the experimental period, aliquots were collected from the mineralization flasks to determine the organic carbon concentration (dissolved and particulate). The global decay coefficient and the coefficients of the three routes admitted by the glucose mineralization model were determined through kinetics fitting. In February (rainy season), the mineralization coefficients were higher ( 10 times) than the mineralization coefficients of July (drought season). In both periods, the anaerobic metabolism showed greater mineralization coefficients (1.4 times in February and 1.1 times in July), than the aerobic one. On the other hand, the carbon immobilization (COP formation) was greater in the aerobic metabolism compared with anaerobic metabolism, in the two periods. The water samples, collected in March/02 in the same place described above, were taken to determine the total and dissolved monosaccharides from polymeric polysaccharide released by bacterioplankton during glucose mineralization. These samples were filtered, enriched with glucose and incubated at 20ºC during 30 days, under aerobic conditions. During that period, aliquots were colleted from the mineralization flasks to determine the monosaccharides concentration. The monosaccharides: arabinose, fucose, galactose and rhamnose were found. Rhamnose showed the greater amount in comparison with other monosaccharides.